Integrated mental health services in China: challenges and planning for the future - Liang, Di; Mays, Vickie M; Hwang, Wei-Chin (Health policy and planning, 2018)
Eager to build an integrated community-based mental health system, in 2004 China started the ‘686 Programme’, whose purpose was to integrate hospital and community services for patients with serious mental illness. In 2015, the National Mental Health Working Plan (2015–2020) proposed an ambitious strategy for implementing this project. The goal of this review is to assess potential opportunities for and barriers to successful implementation of a community-based mental health system that integrates hospital and community mental health services into the general healthcare system. We examine 7066 sources in both English and Chinese: the academic peerreviewed literature, the grey literature on mental health policies, and documents from government and policymaking agencies. Although China has proposed a number of innovative programmes to address its mental health burden, several of these proposals have yet to be fully activated, particularly those that focus on integrated care. Integrating mental health services into China’s general healthcare system holds great promise for increased access to and quality improvement in mental health services, as well as decreased stigma and more effective management of physical and mental health comorbidities. This article examines the challenges to integrating mental health services into China’s general healthcare system, especially in the primary care sphere, including: accurately estimating mental health needs, integrating mental and physical healthcare, increasing workforce development and training, resolving interprofessional issues, financing and funding, developing an affordable and sustainable mental health system, and delivering care to specific subpopulations to meet the needs of China’s diverse populace. As China’s political commitment to expanding its mental health system is rapidly evolving, we offer suggestions for future directions in addressing China’s mental health needs. 为建立以社区为基础的综合精神卫生体系, 中国于 2004 年启 动了” 686 项目”, 旨在整合重性精神疾病的医院和社区服 务。2015 年, 《全国精神卫生工作规划 （2015-2020 年）》 提出了实施这一项目的宏伟战略。本综述目的是评估将医院 和社区精神卫生服务整合到卫生体系中, 建立以社区为基础的 精神卫生体系可能面临的机遇和障碍。我们回顾了 7066 份 中英文文献, 包括同行审议的学术文献、精神卫生政策的灰色 文献, 以及政府和决策机构的文件。虽然中国提出了一系列有 创造性的项目来应对精神卫生负担, 但有部分提案尚未完全启 动, 尤其是关注综合服务的项目。将精神卫生服务纳入中国的 卫生保健体系有望提高精神卫生服务可及性, 改善精神卫生服 务质量, 消除精神疾病污名, 更有效地管理躯体合并精神疾 病。本文探讨了将精神卫生服务整合入中国卫生保健体系的 挑战, 尤其是在初级保健方面, 包括：准确估计精神卫生需求, 整合精神和躯体疾病保健, 加强人员发展和培训, 解决跨专业 问题, 筹资和资金, 建立可负担、可持续的精神卫生体系, 以 及为特定人群提供服务从而满足中国百姓多样化需求。随着 中国政府越来越重视健全精神卫生体系, 我们为未来解决中国 精神卫生需求的方向提供了建议。 Deseosa de construir un sistema integrado de salud mental basado en la comunidad, China inició en el 2004 el ‘Programa 686’, cuyo propósito era integrar servicios hospitalarios y comunitarios para pacientes con enfermedades mentales graves. En 2015, el Plan Nacional de Salud Mental (2015-2020) propuso una estrategia ambiciosa para la implementación de este proyecto. El objetivo de esta revisión es evaluar las potenciales oportunidades y barreras para la implementación exitosa de un sistema de salud mental basado en la comunidad que integre los servicios de salud mental del hospital y de la comunidad al sistema de atención médica general. Examinamos 7,066 fuentes tanto en inglés como en chino: la literatura académica revisada por pares, la literatura ‘gris’ sobre políticas de salud mental y los documentos del gobierno y de las agencias de formulación de políticas. Aunque China ha propuesto un número de programas innovadores para abordar su carga de salud mental, varias de estas propuestas aún no se han activado por completo, en particular las que se centran en la atención integrada. La integración de los servicios de salud mental en el sistema general de salud de China es una gran promesa para obtener un mayor acceso y una mejora de la calidad en los servicios de salud mental, así como un menor estigma y un manejo más efectivo de las comorbilidades físicas y de salud mental. Este artículo examina los desafíos de la integración de servicios de salud mental en el sistema de salud general de China, especialmente en la esfera de atención primaria, que incluye: estimar con precisión las necesidades de salud mental, integrar la salud mental y física, aumentar el desarrollo y capacitación de la fuerza de trabajo, la resolución de problemas interprofesionales, el financiamiento y los fondos, desarrollar un sistema de salud mental asequible y sostenible, y brindar atención a subpoblaciones específicas para satisfacer las necesidades de la población diversa de China. A medida que el compromiso político de China para expandir su sistema de salud mental evoluciona rápidamente, ofrecemos sugerencias para direcciones futuras para abordar las necesidades de salud mental de China.